Exercise-induced myokines: a brief review of controversial issues of this decade. Issue 1 (2nd January 2018) - Son, Jun Seok; Chae, Song Ah; Testroet, Eric D.; Du, Min; Jun, Hyung-pil
ABSTRACT: Introduction : Myokines, known to mediate metabolism, inflammation, and other pathophysiological conditions, have been widely investigated, including myokines induced by exercise. However, among published literature, there is substantial inconsistency in the quantification of exercise-induced myokines. Here, we summarized and compared published data regarding the effects of exercise on commonly studied myokines including apelin, Brain-derived neurotrophic factor (BDNF), Interleukin-15 (IL-15), irisin, and Secreted protein acidic and rich in cysteine (SPARC) during the last decade and discussed possible reasons for discrepancy in these reports. Areas covered : A search on PubMed for original articles published in this decade was conducted, focusing on the impacts of exercises on myokines and metabolic and age-related disorders. Beneficial relationship between skeletal muscle plasticity and myokines due to exercise is also discussed. Expert commentary : Based on these analyses, exercise induces the secretion of a number of myokines, which has positive effects on metabolic diseases or age-related muscle atrophy (sarcopenia). However, among published reports, there is wide discrepancy in the quantification of myokines induced by exercise, which could be due to timing of sample collection, pre-analytic sample processing, analytical method, and calculation and other factors. Thus, these factors need to be considered in future studies on exercise induced myokines.